Using International Trade data for evaluating the Product Specific Competitiveness and Supplied Product Quality of Countries. A Succeessful Example of Applied Theory - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
This paper proposes a simple regression-based method for reducing the complexity of decisions in the international procurement process. Based on foreign trade data, the method uses indicators, which allow a product specific cross-section and longitudinalsection valuation of the international competitiveness and the supplied product quality of all potential supplier countries. The method thus provides a variety of information for procurement departments, including the present level and the dynamic of competitiveness and product quality for the potential supplier countries within every product group of the international product nomenclature (Combined System and the Harmonised System). Potential supplier countries --the companies of which have proven to be particularly competitive in the different product quality stages-- are identified. This pre-selection of countries enables the companies to limit their search for potential suppliers to the selected supplier countries. High search costs are subsequently reduced and trend prognoses can be constructed.